The role of free surfaces on the formation of prismatic dislocation loops. (1st July 2015) - Munday, Lynn B.; Crone, Joshua C.; Knap, Jaroslaw
Abstract : Prismatic punching is a process where voids grow through the nucleation and emission of prismatic dislocation loops (PDLs). In this work we employ dislocation dynamics to determine the effect of image stresses produced by the void's free surface on PDL formation in a face-centered cubic lattice. We find that image stresses cause PDL formation to fall into two distinct pressure regimes. In the low pressure regime, image stresses dominate dislocation cross-slip, reducing the PDL's size and formation rate.